Behavioral responses of domestic cats to human odor - Yutaro Miyairi; Yuichi Kimura; Koji Masuda; Hidehiko Uchiyama (PLoS ONE, 2025)
People all around the world live with cats and cats engage in many social behaviors toward their owners. Olfaction is one of the most important sensory abilities in cats, yet its role in recognizing humans remains unclear. In this study, we assessed the role and characteristics of olfaction in the discrimination of known or unknown humans by cats using ethological methods. Whether cats exhibit a lateralization of nostril use in response to a variety of olfactory stimuli, exposure experience, inter alia, was investigated. Cats were simultaneously presented with three odor stimuli: that of a known person (owner), an unknown person, and a blank control. Responses to the cat 2 scale (Feline Five) and the cat–owner relationship scale (CORS) were collected from cat owners through questionnaires. It was observed that cats spent a substantially longer time sniffing the odor of an unknown person than that of a known person, indicating the use of their sense of smell to distinguish between heterospecific (human) individuals. While responding to odor stimuli from unknown humans, the cats displayed marked lateralization in the use of one nostril or another. An association was observed between the first odor the cat sniffed among known, unknown, and blanks and the personality score. A strong correlation was found between the number of repetitive sniffing odors and personality scores in male cats. No association was evident between the cat’s behavior and the cat–owner relationship score. Rubbing of their faces against an object immediately after sniffing it was observed and thus a possible relationship between the olfactory exploration and subsequent rubbing (odor-marking) behavior in cats is postulated. However, this relationship warrants further investigation along with the theory of whether cats are able to recognize a specific person from olfactory cues.